KONSTRUK HATI MASYARAKAT IMOGIRI TERHADAP RITUAL MONG-MONG PEDET (APLIKASI TEORI EVANS-PRITCHARD) - Fauziah, Wiwi (UIN Sumatera Utara Medan, 2023)
His study examines sacred phenomenon of the Imogiri village community inBantul district, Yogyakarta. This phenomenon is a ritual to welcome the birth oflivestock such as goats, cows and buffalo or called mong-mong pedet. Using theEvans-Pritchard's viewofempiricalanthropologicalapproach, this researchwill thoroughly examine the mong-mong pedet ritual by going directly to thefield. Thus, focus of this research does not only touch on religion, but all aspectssurrounding the sociology of the Imogiri village community. This research is aqualitative-empirical study that uses two sources of material. The primary datasourcesfrominterviewswith residentsofImogiri.Thenthe secondarydatasources come from support information such as books, journals and other. Thisstudyfoundthatthemong-mongpedetritualisanacculturationofreligionsand cultures thatstillexistandare sacredinthemidstofincreasingly moderndevelopments.Eventhoughtheritualseenasprimitive,theconstructoftheheartoftheImogiripeopleseesthemong-mongcalfritualasaformofcommunity gratitude for something received, namely the birth of a child fromtheir livestock. It shows the position of reasoning of the Imogiri people that theritualarerational and normalfor them.